Chlorobenzene: A Processing Solvent Enabling the Fabrication of Perovskite Solar Cells with Consecutive Double‐Perovskite and Perovskite/Organic Semiconductor Bulk Heterojunction Layers. Issue 5 (25th February 2019) - Wang, Jiandong; Yao, Xiang; Xiao, Wen‐Jing; Bai, Yang; Xu, Zi‐Wen; Lin, Jian; Li, Wei‐Shi
Abstract : Chlorobenzene (CB), which has been used as an anti‐solvent, is demonstrated here as a processing solvent for the fabrication of perovskite films and solar cells. This approach results from the unexpected finding that butylamine‐bound organolead iodides can be dissolved in CB to form precursor solutions. Together with previously established perovskite composition transformation methods, not only conventionally structured perovskite solar cells (PSCs) with a (CH3 NH3 )PbI3 active layer but also nonconventionally structured devices with a consecutive (CH3 NH3 )PbI3 /(C4 H9 NH3 )2 PbI4 double layer or a mixed poly(triaryl amine) (PTAA) and (CH3 NH3 )PbI3 bulk heterojunction layer are successfully prepared and demonstrated with an optimal efficiency of 16.44%. This is the first time that nonpolar solvents are used for perovskite material processing, which can remove the solvent limitation and open a new avenue for designing and preparing perovskite devices with desired structures. Abstract : Alkyl‐amine bound organolead halides are soluble in chlorobenzene. This finding prompts the authors to prepare perovskite precursor solutions using this nonpolar solvent and produce perovskite devices from conventionally layered to specially designed structures with consecutive (CH3 NH3 )PbI3 /(C4 H9 NH3 )2 PbI4 double layers or PTAA@(CH3 NH3 )PbI3 blend layers. This study is the first to use a nonpolar solvent for perovskite material processing, device fabrication, and architecture design.